2011
DOI: 10.5402/2011/750676
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Laser Microsurgery for Early Glottic Cancer

Abstract: Objectives. To assess the outcome of transoral laser-assisted microsurgery (TLM) with regards to local and distant tumour control, quality of voice and swallowing. Design. Retrospective review of patients with five-year follow-up period. Setting. Royal Derby Hospital Head and Neck Department. Participants. All patients undergoing TLM with a diagnosis of Tis, T1, or T2 glottic tumour following endoscopic biopsy. Main Outcome Measures. Speech, swallowing, cancer-free survival, laryngectomy-free survival, and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Furthermore, we have not explored the functional outcomes of primary transoral laser microsurgery in this study. However, our institution has previously reported good voice and swallowing outcomes in early‐stage glottic cancer . Further analysis of the functional outcomes in late‐stage disease is needed.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we have not explored the functional outcomes of primary transoral laser microsurgery in this study. However, our institution has previously reported good voice and swallowing outcomes in early‐stage glottic cancer . Further analysis of the functional outcomes in late‐stage disease is needed.…”
Section: Discussionmentioning
confidence: 96%
“…Our histological reporting also complied with the recommended standards for three-dimensional assessments, including the deep margin. However, other factors such as trauma from surgical instruments or tissue handling, artefacts from histopathological slide preparation and thermal damage from laser use can lead to difficulties in margin interpretation 14 , 15 . The deep margin could not be assessed with confidence in almost 10 per cent of our cases owing to thermal damage.…”
Section: Discussionmentioning
confidence: 84%
“…However, other factors such as trauma from surgical instruments or tissue handling, artefacts from histopathological slide preparation and thermal damage from laser use can lead to difficulties in margin interpretation. 14,15 The deep margin could not be assessed with confidence in almost 10 per cent of our cases owing to thermal damage. Makki et al reported a significantly higher degree of artefacts with transoral laser microsurgery compared with cold steel excision, which caused difficulty in assessing specimens; however, positive margins could still be confidently interpreted.…”
Section: Discussionmentioning
confidence: 97%
“…45% of patients in this study had mild or moderate voice change. 15 The quality of voice after TLM depends on the degree of resection required and more superficial tumours have a better outcome. 15 In a study by Ahmed et al, the laryngeal preservation rate for patients who initially received KTP laser treatment was 46 out of 47 patients (98%).…”
Section: Discussionmentioning
confidence: 99%
“…15 The quality of voice after TLM depends on the degree of resection required and more superficial tumours have a better outcome. 15 In a study by Ahmed et al, the laryngeal preservation rate for patients who initially received KTP laser treatment was 46 out of 47 patients (98%). 1 Of the cohort who received primary radiation, the laryngeal preservation rate was 36 out of 40 patients (90%).…”
Section: Discussionmentioning
confidence: 99%